2005
DOI: 10.1128/mcb.25.16.7344-7356.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Crucial Site for Synoviolin Expression

Abstract: Synoviolin is an E3 ubiquitin ligase localized in the endoplasmic reticulum (ER) and serving as ERassociated degradation system. Analysis of transgenic mice suggested that synoviolin gene dosage is implicated in the pathogenesis of arthropathy. Complete deficiency of synoviolin is fatal embryonically. Thus, alternation of Synoviolin could cause breakdown of ER homeostasis and consequently lead to disturbance of cellular homeostasis. Hence, the expression level of Synoviolin appears to be important for its biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 63 publications
4
30
0
Order By: Relevance
“…3). In addition, our recent analyses of the synoviolin promoter also demonstrated that transcriptional regulation of the gene is critical for cell growth and apoptosis in vitro (10), which strongly suggests that the amount of Synoviolin is critical to the regulation of synovial cell overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…3). In addition, our recent analyses of the synoviolin promoter also demonstrated that transcriptional regulation of the gene is critical for cell growth and apoptosis in vitro (10), which strongly suggests that the amount of Synoviolin is critical to the regulation of synovial cell overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Genes located near these loci perform a broad range of functions including DNA synthesis and repair (REV3L [48] and PCNA [73]), transcription (XPMC2H [55], HNRPUL1 [45], BANP [67], ATF7 [64], ZNF215 [3], and MYC [21]), mitochondrial function (CA5A [58] and COX7A2L [79]), and mitotic spindle assembly (CDCA8) (16). One target has direct involvement in the secretory functions of the cell (COH1) (41), while another target has a direct link to the unfolded protein response (UPR) (SYVN1) (75). CGI ChIP-chip to identify p53 targets genes therefore identifies a broad range of potential target genes that may mediate direct effects on p53 function.…”
Section: Resultsmentioning
confidence: 99%
“…The Ets binding site (EBS) is determined to be the crucial site for synoviolin transcription in vivo and in vitro, and GABP, a transcription factor known to be down stream of MAP kinases such as JNK and ERK, is proved to be bind to it. 51 The MAP kinase signals are activated in both neoplasm and RA, thus these signal may induce constitutively high expression of Synoviolin in these diseases. 52,53 Similar pathogenic mechanism for neoplasm progression has been actually implicated in a human disease.…”
Section: Impact Of Synoviolin Dysregulationmentioning
confidence: 99%